THE ANALYSIS OF PAVING BLOCK QUALITY CONTROL WITH VARIABLE APPROACHES (Study Of CV. Proton In Palu City) - Pratiwi, Rika Yunita; Kaseng, Saharuddin; Asngadi, Asngadi (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2024)
The purpose of this study was to determine how the quality control limit of Paving Block with Control By Variable Approach at CV. Proton in Palu City and find out whether the Paving Block quality process with the Control By Variable Approach is within the control limits. The research was conducted at CV. Proton in Palu City. The type of research used in this research is quantitative analysis. Data collection methods are carried out by interviews and field surveys. The sample in this study was 4 pieces of Paving Block / day for 20 days of research which was tested with a pressure load test. Data analysis was carried out using Check Sheet and control map with Control By Variable approach (X-bar and R-Chart). The results prove that the Paving Block quality process with the Control By Variable approach at CV. Proton is within the control limits. This is indicated by the results of UCL, CL, LCL on the X-bar and R-chart with control limits of 3-sigma and 2-sigma), which means that the quality control of this Paving Block is within the control limits so that the quality of the Paving Block belonging to CV. Proton is said to be good, and for both the graph results on the X-bar and R-chart show that almost all points are within the control limits, this is indicated by the absence of points that go outside the control limits, namely UCL and LCL, so that the quality control of the Paving Block owned by CV Proton is good.